Historical and ongoing hybridisation in Southern South American grassland species - Giovanna C. Giudicelli; Pedro H. Pezzi; Sebastián Guzmán-Rodriguez; Caroline Turchetto; Aureliano Bombarely; Loreta B. Freitas (Scientific Reports)
Abstract Natural hybridisation in plants can impact genetic and morphological diversity, including the emergence of better-adapted new populations and the potential extinction of some lineages involved in this intricate process. Under progressive global warming, species often need to migrate to newly suitable areas, which may be an additional challenge for species with low dispersal ability. Throughout the search for new environments, previously allopatric lineages can come into secondary contact and eventually hybridise if reproductive isolation is incomplete. Here, we focused on two taxa representing the natural herbaceous component of southern South American lowland grasslands. We aimed to evaluate the impact of contact zones and potential hybridisation on the evolutionary relationships and population dynamics. We used single nucleotide polymorphisms and morphological data of multiple individuals from allopatric and contact zones between taxa to shed light on hybridisation patterns and demographic scenarios. Our results indicated that the contact zones impact taxa’s genetic and morphological diversity, and each contact zone had different patterns of genetic diversity and morphology, constituting stable populations that potentially reflect hybridisation events occurring at distinct evolutionary times.